2014
DOI: 10.1002/jcph.259
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of paracetamol across the human age‐range from (pre)term neonates, infants, children to adults

Abstract: In order to characterize the variation in pharmacokinetics of paracetamol across the human age span, we performed a population pharmacokinetic analysis from preterm neonates to adults with specific focus on clearance. Concentration-time data obtained in 220 neonates (post-natal age 1-76 days, gestational age 27-42 weeks), infants (0.11-1.33 yrs), children (2-7 yrs) and adults (19-34 yrs) were analyzed using NONMEM 7.2. In the covariate analysis, linear functions, power functions, and a power function with a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 34 publications
5
58
1
Order By: Relevance
“…In particular, our findings for our BCS class I compounds, theophylline and paracetamol, indicate that both compounds are absorbed to a similar extent at different absorption sites throughout the GI tract ( Figure 2) [33], which is reflected by the very similar absorption half-life and k a values in adults ( Table 1). Given that theophylline is almost completely absorbed (f a~1 ) and that there are no known absorption transporter effects for theophylline [56], it seemed reasonable to assume that the maturation function identified for the changes in oral drug absorption in paracetamol after birth can also be applied to theophylline.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In particular, our findings for our BCS class I compounds, theophylline and paracetamol, indicate that both compounds are absorbed to a similar extent at different absorption sites throughout the GI tract ( Figure 2) [33], which is reflected by the very similar absorption half-life and k a values in adults ( Table 1). Given that theophylline is almost completely absorbed (f a~1 ) and that there are no known absorption transporter effects for theophylline [56], it seemed reasonable to assume that the maturation function identified for the changes in oral drug absorption in paracetamol after birth can also be applied to theophylline.…”
Section: Discussionmentioning
confidence: 60%
“…Paracetamol There are a number of paediatric popPK models for paracetamol published in the literature, which range from simple one compartment models to more complex three compartment models [31][32][33]. The model by Anderson et al [7], which contains the maturation function introduced in Equation [1], is a one compartment model.…”
Section: Bcs Class I Drugs (High Solubility High Permeability)mentioning
confidence: 99%
“…Pharmacokinetics studies on intravenous paracetamol in preterm infants also suggest that a loading dose of 20 mg/kg intravenous paracetamol for neonates with postconceptional ages of 28-32 weeks and body weights above 1.5 kg is sufficient for pain relief [15]. Pharmacokinetics/pharmacodynamics data in older infants suggest a target plasma concentration of >9 mg/L [13]. Our study showed plasma concentrations >9 mg/L in 95% of all subjects.…”
Section: Discussionmentioning
confidence: 99%
“…While there are data from pharmacokinetics studies [12,13], the pharmacodynamics of paracetamol in neonates are poorly described. Allegaert et al [14] showed a reduction of pain after 20 mg/kg of paracetamol in preterm and term infants suffering from delivery trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was therefore to evaluate the predictive performances of three published PK models [2,3,6] for i.v. acetaminophen and to build a compartmental population PK model for i.v.…”
Section: Introductionmentioning
confidence: 99%